Forest managers’ perspectives on environmental changes in the biosphere reserve Mura-Drava-Danube - Sallmannshofer, Markus; Damjanić, Rok; Vacik, Harald; Westergren, Marjana; Baloh, Tjaša; Božič, Gregor; Ivanković, Mladen; Kovács, Gyula; Lanšćak, Miran; Lapin, Katharina; Nagy, László; Ostoić, Silvija Krajter; et al. (Frontiers in Forests and Global Change, 2023)
Riparian forests are particularly vulnerable to environmental change and anthropogenic influences because they are highly dynamic ecosystems, thus proper adaptation measures are crucial. The implementation of these measures, however, strongly depends on the actor’s perception of the specific problems occurring in such forests. For understanding the constraints of specific interest groups towards different adaptation activities information in this field is essential. In this study, we explore how different types of forest managers, i.e. forestry professionals, forest owners, and conservation managers, perceive the effects of environmental change on forest management in the recently established Transboundary Biosphere Reserve Mura-Drava-Danube by conducting a questionnaire survey. We show that these forest managers are aware of ongoing environmental changes and appraise deteriorating forest conditions, especially after observing changes themselves. Abiotic damage is expected to increase the most, followed by biotic damage, the spread of non-native species, and tree dieback. Nearly 80% of the survey respondents expect further changes and almost all of them intend to adapt their management of forests to mitigate or prepare for these changes. Nevertheless, we show differences in sensitivity to change and willingness to initiate adaptation actions by assessing adaptation thresholds: conservation managers appear generally more tolerant to changes, which results in higher thresholds to initiate management adaptation than forestry professionals and forest owners. Respondents’ selection of target tree species depends on management goals and therefore, we found further differences between forestry professionals and conservation managers. These aspects need to be carefully considered to foster cooperation or develop sustainable management frameworks and adaptation strategies.